Mensuração do capital social em comunidades no interior do Estado de São Paulo - Lopes, Carlos Alberto (2012)
This research presents the measurement of levels of social capital in six interrelated dimensions in three neighborhoods in different cities in São Paulo State. The methodology used a questionnaire with closed questions and covers a total of 81respondents. The theoretical research is centered on Robert D. Putnam with other subsidies from James Coleman and Pierre Boudieu and methodological contributions from researches of Social Capital Thematic Group of World Bank. Derived from the data was set an exploratory index of social capital that is presented as the first step towards the improvement of instruments for research on social capital